Encouraging Young Entrepreneurs to Take Over Family Businesses - Aditya, Farhan (Malacca: Journal of Management and Business Development, 2025)
Naturally, they are crucial to the continuation of the family firm, being young people who inherited it and living in a Strategic location.  Also, whether or not they are prepared to take risks as entrepreneurs will determine the long-term viability of the industrial park.  A qualitative technique is utilized in this study's methodology.  This study's data came from in-depth, semi-structured interviews.  Data collection, editing, and classification are the first steps, followed by analysis and interpretation.  Teens from the Jenang Kelapa Jombang complex whose families run their own businesses are the focus of this investigation.  This study employs Phenomenological Analysis for its data analysis.  There are four steps to data analysis: maintaining the data, interpreting it, summarizing it, and finally, presenting it.  According to this study, the Jenang Kelapa Jombang center's youth have an entrepreneurial mentality that starts at a young age.  Being a member of the family company molded their behavior and mentality, so it came easily to them.  Another thing that came out of this study is that people can run their family business, follow in their parents' footsteps as entrepreneurs, and even have a post-graduate degree if they really want to.